Diamondoids in petroleum: Their potential as source and maturity indicators. (October 2021) - Jiang, Wenmin; Li, Yun; Fang, Chenchen; Yu, Zhiqiang; Xiong, Yongqiang
Graphical abstract: Highlights: Pyrolysis experiments on four organic matter types simulate diamondoid evolution. Principal component analysis explains the main factors affecting diamondoid indices. PCA-Fisher discriminant analysis model objectively identifies oil source types. PCA-regression analysis model quantitatively predicts oil thermal maturity. Abstract: Assessing the origins and thermal maturity of oils is an important issue in applied petroleum geochemistry. In this study, we extracted information regarding the sources and thermal maturity of oils from diamondoid data using multivariate statistical analysis based on four series of thermal simulation experiments conducted on Type I, II, and III kerogens and a crude oil. Using principal component analysis (PCA) and discriminant analysis (DA), we established the relationship between diamondoid indices and kerogen type, which was then used to identify the source of oils in some oil fields in China. PCA and regression analysis (RA) were used to determine the quantitative relationship between diamondoid indices and thermal maturity, which was then used to estimate the thermal maturity of the studied oils. Our results indicate that this approach is effective for determining the source and maturity of oils, particularly for condensates.